The Mental Health Implications of Transgenerational Trauma Among Refugee Communities in Multan: A Sociopsychological Analysis - Shaista Ajmal; Muhammad Adil; Elsa Khalil; Hina Fatima; Shamsa Kanwal; Aisha Iqbal Khan, (Dialogue Social Science Review (DSSR), 2025)
Study outcomes for refugee mental health in Multan evaluate trauma transmission through generations with special emphasis on the psychological consequences endured by those descended from survivors. The research design implemented mixed methods to study traumatic experiences, PTSD symptoms, depression symptoms, anxiety symptoms and demographic aspects from 150 participants. Results from psychological assessments through recognized standards revealed that 65% of participants experienced moderate to severe PTSD symptoms alongside major depression or anxiety symptoms affecting 59% of participants who underwent 70% traumatic exposure incidents. The analysis confirmed a strong direct connection between parents' experience of trauma (r = 0.72) which produced mental health results in their children (with a very significant p value below 0.01). Research found affected participants from underserved familial backgrounds to display higher psychological distress at 45.3%. Family and community relations showed key importance in developing participant resistance to stress. This research shows how we need culturally appropriate community-based healthcare methods to treat transgenerational trauma in refugee communities across generations.